2019
DOI: 10.1007/s00705-019-04267-0
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of four novel Staphylococcus myoviruses

Abstract: We report here the annotation of the complete genomes of four novel lytic Staphylococcus phages; Stab20, Stab21, Stab22 and Stab23. These phages have double-stranded DNA genomes ranging between 153338-155962 bp in size with terminal repeats of 10814-12304 bp. The genome analysis suggests that they are new phage species within genus Kayvirus in the Spounavirinae subfamily of the Myoviridae family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Our rationale to characterize the Stab phages originally isolated using S. xylosus as enrichment host [31] was based on the facts that Staphylococcus phages generally show wide host spectra, that new S. aureus specific phages are not easy to encounter, and that every phage able to infect clinical S. aureus isolates would be a welcome addition to our collection of potential therapeutic phages.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our rationale to characterize the Stab phages originally isolated using S. xylosus as enrichment host [31] was based on the facts that Staphylococcus phages generally show wide host spectra, that new S. aureus specific phages are not easy to encounter, and that every phage able to infect clinical S. aureus isolates would be a welcome addition to our collection of potential therapeutic phages.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, genome sequence and phylogenetic analyses of phages Stab20, Stab21, Stab22, and Stab23, established that the phages are members of the genus Kayvirus which exclusively contains Staphylococcus phages [31]. Electron microscopy revealed that these phages possess icosahedral heads, long contractile tails with baseplates at the end, and tail fibers extending from the baseplates (Figure 1).…”
Section: Morphologymentioning
confidence: 91%
See 3 more Smart Citations